EXIT (ex utero Intrapartum Treatment) to Airway Procedure for Twin Fetuses With Oropharyngeal Teratomas: Lessons Learned - King, Alice; Keswani, Sundeep G.; Belfort, Michael A.; Nassr, Ahmed A.; Shamshirsaz, Alireza A.; Espinoza, Jimmy; Bedwell, Joshua R.; Mehta, Deepak K.; Doughty, Cara B.; Leong-Kee, Susan Margaret; Lawrence, Julia B.; Sun, Raphael C.; et al. (Frontiers in Surgery, 2020)
Ex utero intrapartum treatment (EXIT) to airway has been described as a safe method to secure challenging fetal airways while on placental support. Herein, we present a unique case of a monochorionic-diamniotic twin pregnancy where both fetuses presented with oropharyngeal tumors requiring airway securement on placental bypass. A multidisciplinary tabletop simulation was convened to allow for personnel coordination between multiple services, OR equipment allocation, and preparation for a range of possible clinical scenarios. A tabletop simulation was chosen for planning since this is a simulation methodology commonly used for preparation in acute, high intensity multidisciplinary situations such as disaster preparation, and allows for exploration of multiple potential scenarios when outcomes are uncertain. The twins were urgently delivered for decreased fetal movement and decelerations in Twin B at 28 weeks 6 days. Twin A was delivered via EXIT to airway while Twin B had debulking of the tumor on placental support, with subsequent airway securement through a tracheostomy. In conclusion, for complex fetal procedures, detailed pre-operative planning with tabletop simulation may be a useful tool in achieving successful patient outcomes.